Effect of hall currents on unsteady magnetohydrodynamic two-ionized fluid flow and heat transfer in a channel - Linga Raju, Temburu; Gowrisankara Rao, V. (Zielona Góra: Uniwersytet Zielonogórski)
An unsteady magnetohydrodynamic(MHD) heat transfer two-fluid flow of ionized gases through a horizontal channel between parallel non-conducting plates, by taking Hall currents into account is studied. The governing partial differential equations that describe the flow and heat transfer under the adopted conditions are solved for the velocity and temperature distributions by a regular perturbation technique.
Keywords: Hall currents; heat transfer; MHD; multi-fluid model; plasma flows